Association of hypertension status and cardiovascular risks with sympathovagal imbalance in first degree relatives of type 2 diabetics. Issue 4 (1st December 2013) - Pal, Gopal Krushna; Adithan, Chandrasekaran; Dutta, Tarun Kumar; Pal, Pravati; Nanda, Nivedita; Lalitha, Venugopal; Syamsunder, Avupati Naga
Abstract Aims/Introduction As reports show cardiovascular (CV) risks in first‐degree relatives (FDR) of type 2 diabetics, and autonomic imbalance predisposing to CV risks, in the present study we have assessed the contribution of sympathovagal imbalance (SVI) to CV risks in these subjects. Materials and Methods Body mass index (BMI), waist‐to‐hip ratio (WHR), basal heart rate (BHR), blood pressure (BP), rate pressure product (RPP), and spectral indices of heart rate variability (HRV) were reordered and analyzed in FDR of type 2 diabetics (study group, n = 293) and in subjects with no family history of diabetes (control group, n = 405). Results The ratio of low‐frequency (LF) to high‐frequency (HF) power of HRV (LF–HF), a sensitive marker of SVI, was significantly increased (P < 0.001) in the study group compared with the control group. The SVI in the study group was due to concomitant sympathetic activation (increased LF) and vagal inhibition (decreased HF). In the study group, the LF–HF ratio was significantly correlated with BMI, WHR, BHR, BP and RPP. Multiple regression analysis showed an independent contribution of LF–HF to hypertension status (P = 0.000), and bivariate logistic regression showed significant prediction (odds ratio 2.16, confidence interval 1.130–5.115) of LF–HF to increased RPP, the marker of CV risk, in the study group. Conclusions Sympathovagal imbalance in the form of increased sympathetic and decreased parasympathetic activity is present in FDR of type 2 diabetics. Increased resting heart rate, elevated hypertension status, decreased HRV and increased RPP in these subjects make them vulnerable to CV risks. SVI in these subjects contributes to CV risks independent of the degree of adiposity.